2009
DOI: 10.1177/112070000901900210
|View full text |Cite
|
Sign up to set email alerts
|

Leg Length and Offset following hip Resurfacing and Hip Replacement

Abstract: We measured and compared critical parameters on antero-posterior radiographs from 28 patients who had undergone hybrid hip replacement (CPS/EPF), with 28 patients who had undergone cemented hip resurfacing (Cormet). All operations were performed by a single surgeon or under his supervision. We measured the femoral offset, acetabular offset, cup height and leg length on pre and post operative radiographs. The mean difference in femoral offset post-operatively was 3.52 mm (95% CI: -1.10 to 8.14 mm) in the hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…FO was restored within ±4 mm in 57% of cases after HR compared to only 25% after THA (P < 0.001); corresponding proportions for LLL restoration within 4 mm were 86% and 60%, respectively (P < 0.001). Similarly, in a retrospective comparison of THA and HR [18], restoration of FO and LLL was significantly better after HR (mean variation in FO, 1.3 mm after HR vs. 3.5 mm after THA; corresponding values for LL, 4.9 mm and 11.9 mm, respectively). In another comparison of THA (n = 50) and HR (n = 40) [19] performed during the same period by the same surgeon, restoration of FO and LL was more reliable with HR.…”
Section: Tablementioning
confidence: 77%
See 1 more Smart Citation
“…FO was restored within ±4 mm in 57% of cases after HR compared to only 25% after THA (P < 0.001); corresponding proportions for LLL restoration within 4 mm were 86% and 60%, respectively (P < 0.001). Similarly, in a retrospective comparison of THA and HR [18], restoration of FO and LLL was significantly better after HR (mean variation in FO, 1.3 mm after HR vs. 3.5 mm after THA; corresponding values for LL, 4.9 mm and 11.9 mm, respectively). In another comparison of THA (n = 50) and HR (n = 40) [19] performed during the same period by the same surgeon, restoration of FO and LL was more reliable with HR.…”
Section: Tablementioning
confidence: 77%
“…Before surgery At last follow-up P value Oxford hip score [12] 39.5 ± 4.2 (28-50) 14.1 ± 1.9 (12)(13)(14)(15)(16)(17)(18)(19) < 0.001 a Harris hip score [13] 42.3 ± 8.2 95.4 ± 7.9 (74-100) < 0.001 a Merle d'Aubigné-Postel score [14] 11.1 ± 1.5 (6)(7)(8)(9)(10)(11)(12)(13)(14) 17.6 ± 0.7 (15-18) < 0.001 a Devane activity score [15] 3.0 ± 0.7 (2-5) 4 ± 0.7 (2-5) < 0.001 a UCLA activity score [16] 5.9 ± 1.3 (3-10) 8 ± 1.4 (5-10) < 0.001 a…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported decreased mean horizontal offsets following hip resurfacing arthroplasty of between 3.3 and 8.4 mm when compared with disease-free contralateral hips [154,157,158]. However, other authors have reported that resurfacing more accurately reproduced native horizontal femoral offset compared with total hip arthroplasty [154,[158][159][160], which frequently produced a larger increase in this measurement. Most authors have reported postoperative mean femoral offset values within a few millimeters of the anatomic values, suggesting that any differences are clinically unimportant in properly selected patients.…”
Section: Potential Disadvantagesmentioning
confidence: 91%
“…Recent evidence has suggested that the evolution of HR designs and surgical techniques has led to HRs with lower wear and improved survivorship (6). Hip resurfacing is associated with less alteration in host anatomy and biomechanics, resulting in less change in leg length and offset (7). There is evidence that HR can be safely converted to a THA should there be a failure on the femoral side (8).…”
Section: Introductionmentioning
confidence: 99%